2018
DOI: 10.1371/journal.pone.0193767
|View full text |Cite
|
Sign up to set email alerts
|

The effect of concentric constriction of the visual field to 10 and 15 degrees on simulated motor vehicle accidents

Abstract: PurposeTraffic accidents are associated with the visual function of drivers, as well as many other factors. Driving simulator systems have the advantage of controlling for traffic- and automobile-related conditions, and using pinhole glasses can control the degree of concentric concentration of the visual field. We evaluated the effect of concentric constriction of the visual field on automobile driving, using driving simulator tests.MethodsSubjects meeting criteria for normal eyesight were included in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Szlyk and colleagues (2005) found increased simulated crash risk was associated with greater binocular visual field loss [13], where 57% of glaucoma drivers with less than 10 degrees of total peripheral visual field were involved in simulator accidents. Using glasses to artificially constrict concentric vision, Udagawa and colleagues showed that the number of driving simulator accidents was significantly higher in drivers with vision constricted to 10 and 15 degrees of visual angle, where greater visual constriction was associated with higher crash rates with vehicles approaching from the visual periphery [35]. Kwon and colleagues demonstrated increased crash risk in glaucoma drivers with binocular visual field loss in upper, lower, and leftbut not rightvisual fields [6], though how visual field loss contributed to crashes remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Szlyk and colleagues (2005) found increased simulated crash risk was associated with greater binocular visual field loss [13], where 57% of glaucoma drivers with less than 10 degrees of total peripheral visual field were involved in simulator accidents. Using glasses to artificially constrict concentric vision, Udagawa and colleagues showed that the number of driving simulator accidents was significantly higher in drivers with vision constricted to 10 and 15 degrees of visual angle, where greater visual constriction was associated with higher crash rates with vehicles approaching from the visual periphery [35]. Kwon and colleagues demonstrated increased crash risk in glaucoma drivers with binocular visual field loss in upper, lower, and leftbut not rightvisual fields [6], though how visual field loss contributed to crashes remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced visual field or FoV extent is associated with decreased spatial awareness, 12,13 pedestrian mobility, [14][15][16][17] and driving, [18][19][20][21] presumably because the available information is reduced. A major impact of the restricted FoV is the loss of peripheral information, where peripheral was a function of the FoV center.…”
Section: Discussionmentioning
confidence: 99%
“…Although peripheral vision has many limitations as compared to foveal vision, including local ambiguity of the location and phase of features, 22 the gist of a scene can be obtained quickly from peripheral vision. 23,24 Although the ability to perform visionrelated tasks decreases as FoV reduces, [12][13][14][15][16][17][18][19][20][21] the amount or proportion of visual content necessary for recognition or comprehension of visual content is not clear. In a clever and evocative study, Ullman et al 25 quantified the transition in recognition rate from a minimal recognizable configuration (MIRC) image to a nonrecognizable descendant (by sequentially cropping 20% of the image).…”
Section: Introductionmentioning
confidence: 99%
“…To imitate advanced peripheral visual field impairment, a special eyeglass was used during the experiment [20,[46][47]. It comprised a frame with a 1-mm pinhole lens (Fig 1) that contracts the participants' binocular visual field angle to approximately 10˚ (Fig 2).…”
Section: Apparatusmentioning
confidence: 99%